(untitled) (Terr@ Plural, 2019)
Urban development is increasing across the Globe and having major impacts on the life histories of organisms, including their responses to the seasonality of the environment. Modified phenology is recognized as one of the more visible impacts of climate change, easy to study as well as to relate as a story to the public. Due to the location of the main academic centres, the main sources of data often come historically from the countryside, and more recently from metropolises and big cities in the Northern Hemisphere. However, for a better understanding of changes in seasonality at a global scale we recommend gathering more data from medium-sized towns and cities, especially in tropical regions.